Determinants of employment-based private health insurance coverage in Denmark - Astrid Kiil (University of Oslo, 2011)
This study estimates the determinants of having employment-based private health insurance (EPHI) based on data from a survey of the Danish workforce conducted in 2009. The study contributes to the literature by exploring the role of satisfaction with the tax-financed health care system as a potential determinant of EPHI ownership and by taking into account that some employees receive EPHI free of charge, while others pay the premium out of their pre-tax income and thus make an actual choice. The results indicate that the probability of having EPHI is positively affected by private sector employment, size of the workplace, whether the workplace has a health scheme, income, being employed as a white-collar worker, and age until the age of 49, while the presence of subordinates, gender, education level, membership of 'denmark' and living in the capital region are not significantly associated with EPHI coverage. As expected, the characteristics related to the workplace are by far the quantitatively most important determinants. The association between EPHI and self-assessed health is found to be quadratic such that individuals in good self-assessed health are more likely to be covered by EPHI than those in excellent and fair, poor or very poor self-assessed health, respectively. Finally, the probability of having EPHI is found to be negatively related to the level of satisfaction with the tax-financed health care system. The findings of the study are not affected notably by distinguishing empirically between employees who receive EPHI free of charge and those who pay the premium out of their pre-tax income.   Link to Appendix